SURGICAL PROCEDURE OF IMPACTED MANDIBULAR CANINE- CASE REPORT - Ilijev, Aneta; Markovska Arsovska, Mirjana; Temelkova, Simona; Mencheva, Zhaklina; Stojanova, Irena; Tosevska, Natasha (Journal of Morphological Sciences, 2025)
Failure of tooth eruption into the oral cavity, because of either insufficient space or the presence of an entity blocking its path of eruption, may lead to different conditions such as impaction, transmigration, retention, or malposition/displacement. The occurrence of impaction and/or non-eruption of mandibular canines is unusual, with prevalence rates from 0.05 to 0.4%.2 There are different methods for performing corticotomy, open and closed method.The aim of this case presentation is to show the closed method of corticotomy performed on the mandibular canine as a rare position of impacted teeth. In the case report, which was performed in 17 years old girl, It`s been used a closed surgical approach of corticotomy with placing a brace during the intervention. Control examinations were performed on the second and seventh postoperative days, when the sutures were removed. The postoperative curse was without any complication, with no pain, redness or oedema. The closed surgical approach of corticotomy is a minimally invasive technique. The side effects of the procedure are minimal. Key words: corticotomy, eruption, alveolar ridge, impacted canine, braces.